(untitled) (Collection of scientific works «Modern structures of metal and wood», 2025)
The need for inspection of building structures containing the fragment of the floor slab in the car park of a residential building arose due to appearance of damage. A fragment of the concrete floor slab was inspected, calculations for the slab were performed in accordance with the requirements of current regulatory documents, its technical condition was determined, and a conclusion was made concerning possibility for further operation. During the research, a regulatory procedure for assessing the technical condition and load- bearing capacity of operated structures was applied. The results of performed survey, calculation and technical condition assessment for building structures containing the slab fragment were presented. It was determined that according to the current regulatory documents containing requirements for technical condition the concrete slab fragment is unusable for operation. The cause for defects and damage in the slab structure was determined: violations of technology for execution of concrete structures in the winter. Based on the research, a design for strengthening the slab structure was developed. Manufacture, transportation and installation of steel reinforcing structures were carried out. Reinforcing the slab using the proposed method made it possible to complete the work in a short time without using wet processes. The load from the weight of the slab structures, according to the develo